Pengaruh Tingkat Pendidikan dan Kepemimpinan terhadap Kinerja Organisasi pada Satuan Kerja Perangkat Daerah (SKPD) Kota Solok - Yulia Ningsih (Faculty of Social Science, Universitas Negeri Padang, 2018)
This study aimed to reveal the effect of the educational level on organizational performance and the effect of leadership on organizational performance of Local Organization Unit (SKPD) in Solok City. This study was an ex-post facto study. The population of this study was all Local Organization Unit in Solok which in total amounted to 40 units. The sample of this study consisted of 36 Local Organization Units determined through simple random sampling. Data were collected through questionnaire with Likert scale that have been tested their validity and reliability. Then the data were analyzed with multiple regression analysis. The results of this study indicated that: (1) the education level did not significantly influence the organizational performance of Local Organization Unit, and (2) leadership had a significantly influence on the organizational performance of Local Organization Unit in Solok City. This study recommended in terms of public sector policies that the managers of Local Organization Units of Solok City needed to motivate their employees to improve their education to a higher level, providing support to their leaders in implementing the leadership function well in terms of influencing, motivating, directing and guiding employees to perform their jobs well.